PENERAPAN METODE EKSPERIMEN HUJAN UNTUK MENGEMBANGKAN SAINS PADA ANAK USIA DINI DI TK A AISYIYAH BUSTANULATHFAL V KOTA PROBOLINGGO - Siti Fatimah; Dirgayunita, Aries (LPPM IAD Probolinggo, 2023)
Abstract Science is the investigation of science with various activities of natural phenomena. The experimental method is to invite children to recognize various things for how the rain process occurs and how to develop their science, information or data through observation of the experimental process. The problem in this study is to determine the ability of science through experimental activities at ABA V Kindergarten. This research uses PTK with a qualitative descriptive approach. Consists of 3 cycles including pre-cycle, cycle 1, and cycle 2 and each cycle is carried out for 2 meetings. This study shows that the results of pre-cycle child assessment observations with a percentage of 25%, and in cycle 1 the ability of children is a percentage of 50%, with the BSH category), in cycle II a percentage of 75% is in the category (BSB). That the result of this rain experiment method, is that the ability and development of children towards science is increasing. Keywords: early childhood, experimental methods, developing science.